Change-of-Direction Assessment in Healthy Adolescent Athletes: Task-Specific Biomechanical Responses Reveal the Optimal Cognitive Dual Task Condition. - Ulman, Sophia; Loewen, Alex M.; Erdman, Ashley L.; Davis, Ava N.; Wilson, Philip L.; Ellis, Henry B. (American Journal of Sports Medicine, 2025)
Background: Injury risk assessments for evaluating competition readiness could be improved by incorporating dual task testing, including decision-making and/or divided attention components, to more closely mirror a competition-like environment. Purpose/Hypothesis: The purpose was to identify the most disruptive (or biomechanically demanding) cognitive load to add to a series of change-of-direction tasks. It was hypothesized that a visual motor response component (unanticipated change in direction) would elicit the greatest biomechanical risk factors across tasks and that changes would be consistent between limbs. Study Design: Cross-sectional study; Level of evidence, 3. Methods: A total of 42 healthy adolescents (aged 14-18 years) were tested in a motion capture laboratory, performing the lateral shuffle, run plant, and run cut tasks with and without dual task conditions including verbal memory (Verbal), visual memory (Visual), and visual motor response (Motor) components. Then, 2-way repeated-measures analysis of variance was performed for each movement task to examine the effects of condition and dominance, as well as a potential interaction effect between condition and dominance, on kinematic and kinetic measures. Results: The Motor condition was found to alter mechanics during the shuffle task, specifically eliciting greater dynamic knee valgus, while the Visual condition had the greatest influence on the run cut task, resulting in a stiffer loading strategy. The run plant task was the least influenced by adding a cognitive load, but a slightly stiffer loading strategy was observed under the Verbal condition. Conclusion: It was concluded that the cognitive load employed for dual task testing was dependent on the movement task being evaluated. The cognitive load type chosen for dual task testing is important and should ideally involve rapid visual processing.